2012
DOI: 10.2135/cropsci2011.12.0629
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reliability of Secondary Traits in Selecting for Improved Grain Yield in Drought and Low‐Nitrogen Environments

Abstract: Grain yield of maize {Zea mays L.) has low heritability under low soil nitrogen (low N) and drought, necessitating the use of secondary traits with strong associations with yield for selection. A base index involving anthesissilking interval, plant and ear aspects, ears per plant, and stay green characteristic is used for selection for yieid under drought and low-N stresses. Reports are contradictory on the reliability of stay green characteristic for selecting for yield under drought stress and of ears per pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 26 publications
7
55
1
3
Order By: Relevance
“…This result suggests that a hybrid with poor score for husk cover and larger ear number per plant is likely to have low grain yield. An earlier report by Badu-Apraku et al (2012), showed similar findings except for the negative correlation between grain yield and ear number per plant. The differences in results could be due to the environmental conditions (drought and low soil nitrogen environments) under which their experiments were conducted as against the environment (favourable condition) that was used in this study.…”
Section: Correlations Among Traits Measuredsupporting
confidence: 72%
See 4 more Smart Citations
“…This result suggests that a hybrid with poor score for husk cover and larger ear number per plant is likely to have low grain yield. An earlier report by Badu-Apraku et al (2012), showed similar findings except for the negative correlation between grain yield and ear number per plant. The differences in results could be due to the environmental conditions (drought and low soil nitrogen environments) under which their experiments were conducted as against the environment (favourable condition) that was used in this study.…”
Section: Correlations Among Traits Measuredsupporting
confidence: 72%
“…Filipovic et al (2014) reported highly significant genetic and phenotypic direct effects of plant height on grain yield. Also, plant height was reported by Badu-Apraku et al (2012) to have a high significant influence on grain yield under drought. Days to silking (0.52), days to anthesis (0.58) and anthesis-silking interval (-0.05) were identified as traits with indirect effects on grain yield via plant height (Fig 1), suggesting that improvement in yield could be achieve indirectly by simultaneously selecting hybrids with increased plant height, longer days to anthesis and silking, and reduced anthesissilking interval.…”
Section: Sequential Path Analysis Of Relationships Among Yield and Yimentioning
confidence: 99%
See 3 more Smart Citations